Cover Image. (9th August 2018) - Hong, Y.; Li, H.‐F.; Romi, F.; Skeie, G. O.; Gilhus, N. E.
Abstract : The cover image, by Yu Hong et al., is based on the Research Article HLA and MuSK‐positive myasthenia gravis: A systemic review and meta‐analysis, DOI:10.1111/ane.12951 .